2001
DOI: 10.1111/j.1447-0756.2001.tb01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction in Late Pregnancy: Cytomegalovirus‐Induced Hepatitis or the HELLP Syndrome?

Abstract: A 27-year-old primiparous preeclamptic woman developed a skin rash in late pregnancy and was persistently febrile for 10 days after giving birth. Blood tests suggested that she developed the HELLP syndrome and had concomitant cytomegalovirus (CMV) infection. Hemolysis, slightly impaired liver function, and thrombocytopenia were explainable by either only the CMV infection or only the HELLP syndrome. A literature review of a limited number of such cases and our case suggests that laboratory data in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…4 HELLPs antigens by suppressing cell-mediated immunity, which may induce a state of increased susceptibility to intracellular pathogen reactivation, such as CMV. 11 Previously, CMV infection was reported in either preeclampsia or HELLPs cases 12,13 and has been reported to initiate Toll-like receptor (TLR) signaling. 14 In CMV-seropositive persons, the monocyte appears to be the major cell type harboring the virus in blood, presumably in a latent state.…”
Section: Introductionmentioning
confidence: 99%
“…4 HELLPs antigens by suppressing cell-mediated immunity, which may induce a state of increased susceptibility to intracellular pathogen reactivation, such as CMV. 11 Previously, CMV infection was reported in either preeclampsia or HELLPs cases 12,13 and has been reported to initiate Toll-like receptor (TLR) signaling. 14 In CMV-seropositive persons, the monocyte appears to be the major cell type harboring the virus in blood, presumably in a latent state.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al [45] reported a case of biopsy-proven CMV hepatitis in a patient receiving prednisone and azathioprine. CMVinduced hepatitis occurs on occasion during pregnancy and the presentation can be similar to the variant of pre-eclampsia known as the HELLP syndrome (hemolysis, elevated liver enzymes, low platelets) [46]. Fetal infection with CMV is a well-known cause of congenital abnormalities, although CMV-induced hepatitis is an uncommon infection of nonimmunosuppressed neonates [47,48].…”
Section: Tissue-invasive Cytomegalovirus Disease Of Other Gastrointesmentioning
confidence: 98%
“…En cas d'atteinte hépatique, l'ictère est peu fréquent, alors que l'hépa-tomégalie est souvent retrouvée [42]. Ces hépatites peuvent être très sévères au cours de la grossesse et mimer des tableaux de HELLP syndrome [43].…”
Section: Hépatite Due Au Cytomégalovirus (Cmv)unclassified